(untitled) (Research, Society and Development, 2023)
The objective of this study is to report the experience lived by medical students in a Basic Health Unit (UBS) in the agreste of Pernambuco through lectures and dynamics on women’s health. This is an experience report at a UBS, in the city of Garanhuns/PE, whose tool used during the intervention were slides, plates and Likert scale to assess its impact. When starting the visits to the UBS, the students noticed a low adherence regarding the gynecological exams performed in the service. For this reason, an extension project was built and, consequently, an intervention for the women in the community was carried out, using the lecture on female care in order to bring the content to women in a clearer and more didactic way. Throughout the event, it was possible to note the public’s interest in basic information about the female body and its multiple functions. Observing this, the need for health actions that reinforce the importance of menstrual monitoring as a care tool and an important indicator for women’s health is evident. According to the reports, some patients did not know how to identify whether they were already in menopause or not, as menstruation appeared irregularly and did not stop completely, even with all the symptoms (age, physiological aspects, hot flushes), and these facts make evident the the need to raise awareness among the female population about the natural cycles of women’s lives. It is important to emphasize the importance of the Health Unit in the clarification process.